Interleukin-22 Level and Vascular Remodeling in Patients with Hypertension in Associated with Abdominal Obesity - Kysylenko, Kateryna; Kovalyova, Olga; Кисиленко, Катерина Володимирівна (My University, 2019)
The purpose of the study was to estimate the interleukin-22 (IL-22) level in the blood serum of hypertensive patients with abdominal obesity (AO), depending on common carotid arteries (CCA) remodeling presence. Ninety-five subjects: 83 hypertensive patients and 12 healthy controls were examined. The patients were divided into two groups, depending on the presence of AO followed by the division of patients into subgroups depending on the intima-media thickness (IMT). For all patients, the following anthropometric parameters were measured: weight, height, waist circumstances (WC), hip circumstances (HC); the body mass index (BMI) and the waist-to-hip ratio (WC/HC) were calculated. The serum IL-22 level was determined in the patients by means of the Bender Medsystems® Human IL-22 Platinum ELISA kit by immunoassay method. Additionally, the patients underwent an ultrasound examination of carotid arteries. The study revealed that the CCA IMT in hypertensive patients with and without AO compared to the control group were significant differences. Serum IL-22 levels in hypertensive patients with AO having IMT ≥ 0.9 mm was statistically higher as compared with patients having IMT < 0.9 mm. The IL-22 levels in hypertensive patients without AO having IMT < 0.9 mm and having IMT ≥ 0.9 mm were significantly exceeds cytokine level in the control group. The obtained results may indicate that the blood serum IL-22 level is associated with a greater degree of vascular wall damage in hyprtensive patient both with and without AO. Higher IL-22 levels in the groups of hypertensive patients both with and without AO, with normal IMT compared with the control group, probably indicate that elevated blood serum IL-22 content can promote an early affection of the vascular endothelium.
Keywords: Interleukin-22; abdominal obesity; vascular remodeling